(untitled) (Orfeu, 2024)
Translation of three original texts by Émile Jaques-Dalcroze (1865-1950), namely: The Spirit of Musical Education (1930), In reply to those who confuse the public eurhythmics exercises of my students with sance exercises (1909), and Duties and Knowledge of the Eurhythmics Teacher (1922). The themes addressed in these manuscripts, as can be seen from the titles, are quite varied, revealing the multifaceted nature of the author’s thinking which boldly moved through several fields in addition to musical art. These translations are preceded by a presentation, in which the historical and biographical context of the author is discussed.